# Thread: Integration Help

1. ## Integration Help

Can someone confirm that the following is correct:

∫〖[e^(-nx) ][x^(s-∞-2)] 〗 dx , limits from x=1 to x=infinity, n is some real integer>=1, and 0<Re(s)<1

What I want to know is, because the equation vanishes for all "x" in the interval x=1 to x=infinity, excluding x=1, can I just bind (e^(-nx)) to e^(-n(1)), leaving:

∫〖[e^(-nx) ][x^(s-∞-2)] 〗 dx=(e^(-n))*∫〖[x^(s-∞-2)] 〗 dx

Any help would be much appreciated.

2. Originally Posted by rman144
Can someone confirm that the following is correct:

∫〖[e^(-nx) ][x^(s-∞-2)] 〗 dx , limits from x=1 to x=infinity, n is some real integer>=1, and 0<Re(s)<1

What I want to know is, because the equation vanishes for all "x" in the interval x=1 to x=infinity, excluding x=1, can I just bind (e^(-nx)) to e^(-n(1)), leaving:

∫〖[e^(-nx) ][x^(s-∞-2)] 〗 dx=(e^(-n))*∫〖[x^(s-∞-2)] 〗 dx

Any help would be much appreciated.
You can't take $\displaystyle e^{-n}$ out as a constant. It's a function of x $\displaystyle e^{-nx}$.